Heritage Tourism in Sumenep: The Role of Need for Uniqueness as a Moderating and Satisfaction as a Mediating Variable - Purwanto, Edy; AR, M. Munir Syam (Yayasan Sinergi Kawula Muda, 2026)
The heritage tourism sector is one of the crucial sectors in economic development in Sumenep Regency. This study investigates the role of need for uniqueness as a moderating variable and satisfaction as a mediating variable in the relationship between touris attraction and revisit intention. The object in this study is focused on heritage tourism in Sumenep such as the sumenep palace, asta tinggi, and jamik mosque sumenep. Purposive sampling was used to choose 230 respondents as the study's sample. The techniques for collecting data were carried out by distributing questionnaires. The Partial Least Squares (PLS)-SEM) program was used to analyze the data. In this study it was found that direct tourist attractions had a positive and significant effect on visitor satisfaction and also revisit intention. Satisfaction has a positive and significant effect on revisit intention. Satisfaction mediates the effect of tourist attraction on revisit intention with the partial mediation category. However, need for uniqueness does not moderate the influence of tourist attractiveness on revisit intention. Therefore, the main findings of this study are expected to enhance the perspectives of tourism managers and support the development of heritage tourism in Sumenep. Furthermore, this study contributes to heritage tourism research by integrating psychological uniqueness and satisfaction into a moderated–mediated framework. The result of this study is also expected to contribute to academics in the management discipline, specifically regarding the context of tourism management.